Enhancing Cultural Identity Through Community Participation: The Wat Khao Yi San In Samut Songkhram Province (Journal of Namibian Studies : History Politics Culture, 2023)
One of the most significant historical landmarks in Samut Songkhram Province is Wat Khao Yi San. It’s historically significant and unique in terms of its architecture and culture compared to other locations. The mixed research methods used in the study were divided into the following groups: Gathering information through villagers' engagement to express viewpoints required by carrying out interviews with three samples, gathering 200 individuals from locals and visitors, and organizing a focus group meeting to compile the data. The study's findings demonstrate that: 1. According to the interview, the main identities are the Old Temple and Grandfather Sriracha almsgiving. 2. Based on the results of the surveys, identification will be given greater weight than other factors ( = 4.583), with the Old Temple receiving the most weight while Grandfather Sriracha almsgiving is ranked second. 3. Results of small group meetings There are suggestions for more publicity through social media.